2021
DOI: 10.3390/toxins13030211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preclinical Properties of Several Available Antivenoms in the Search for Effective Treatment of Vipera ammodytes and Vipera berus Envenoming

Abstract: Snakebites are a relatively rare medical emergency in Europe. In more than half of the annual cases caused by Vipera ammodytes, Vipera berus, and Vipera aspis, immunotherapy with animal-derived antivenom is indicated. Among eight products recently identified as available against European medically relevant species, only Zagreb antivenom, Viperfav, and ViperaTAb have been used almost exclusively for decades. Zagreb antivenom comprises V. ammodytes-specific F(ab′)2 fragments. Viperfav is a polyspecific preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Given the large time span of the study, it should not surprise the reader that the use of obsolete yet effective sera such as the ‘Zagreb’ antivenom, which is not produced anymore. However, while polyvalent sera (that is, derived from multiple viper species) are effective antivenoms for the management of the main European viper species [ 21 ], other monovalent antivenoms may also be administered on the grounds of their cross-reactivity [ 23 ]. That being said, the ‘Viperfav’ (manufacturer: Sanofi-Pasteur MSD, France) antivenom, which is derived from V. ammodytes , V. berus , and V. aspis venom, seems to be the best choice for the treatment of viper bites in Italy, as in Europe, where these viper species reside.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large time span of the study, it should not surprise the reader that the use of obsolete yet effective sera such as the ‘Zagreb’ antivenom, which is not produced anymore. However, while polyvalent sera (that is, derived from multiple viper species) are effective antivenoms for the management of the main European viper species [ 21 ], other monovalent antivenoms may also be administered on the grounds of their cross-reactivity [ 23 ]. That being said, the ‘Viperfav’ (manufacturer: Sanofi-Pasteur MSD, France) antivenom, which is derived from V. ammodytes , V. berus , and V. aspis venom, seems to be the best choice for the treatment of viper bites in Italy, as in Europe, where these viper species reside.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of the anti- V. b. berus antivenom could be improved 11.5 to 23 times by affinity chromatographic purification of its F(ab') 2 antibodies. Recently Kurtovič et al (2021) performed comparative analysis of the safety-related properties and efficacy of a panel of antivenoms against V. ammodytes and/or V. berus envenoming that are currently available, or in development for the European market. They revealed that Viperfav (Sanofi Pasteur SA, Lyon, France) had the best protection against lethal toxicity induced by the venoms of both V. ammodytes and V. berus .…”
Section: Antivenomsmentioning
confidence: 99%
“…In comparison to Zagreb antivenom Viperfav showed 4- to 5-fold weaker protective efficacy. Renewal of Zagreb antivenom production would be of great value ( Kurtovič et al 2021 ).…”
Section: Antivenomsmentioning
confidence: 99%
“…Također važno je spomenuti i zagrebački protuotrov koji se prestao proizvoditi 2014., a pokazao je najveću specifičnu aktivnost te bi njegova ponovna proizvodnja omogućila svim javnozdravstvenim ustanovama dostupnost protuotrova čija je sigurnost i učinkovitost ispitana. 26…”
Section: Prva Pomoć I Liječenje Kod Ugriza Zmijeunclassified